Teaching Reading in Today's Elementary Schools - Burns, Paul C. ; Roe, Betty D. and Ross, Elinor P. (Boston Houghton Mifflin, 1988)
This market-leading text sets the standard for reading instruction and provides preservice teachers with extensive coverage of strategies, examples, and study devices. The book balances new approaches to reading--such as language arts integration and emergent literacy/literacy as a continuum with the more traditional foundations of strong skills and phonics instruction. Coverage of current topics includes assessment standards, teaching diverse learners, technology and the teaching of literacy, and the role of parent-teacher communication in student success.
Include Notes, Index, Appendix and Illstrations.
Keywords: Reading (Elementary) -- United States